Urbanization Transition in Nepal A Case Study of Dipayal Silgadhi Municipality, Doti, Nepal - Panday, Tilak Raj (DMC Research Journal, 2023)
This paper deals with the urbanization transition in Nepal: A Case Study of Dipayal Silgadhi Municipality analyzing the social and economic status of the residents of Dipayal Silgadhi Municipality, especially in new adjoining areas. This study is based on primary data which are derived from field surveys through household surveys, field observations, and in-depth interviews. For the household survey, 45 households were taken from ward no. 9, Dipayal Silgadhi Municipality with the help of convenience non-probability sampling. Dipayal Silgadhi municipality has rural characteristics. Most of the part is occupied by rural areas. Similarly, people do not feel like living in a municipal area in the new adjoining area. There is a lack of occupational diversification. Most people engage in primitive agriculture and another main livelihood strategy is foreign labor migration. There is also a lack of trade specialization and diversification which is the main criteria of urban development. This study is helpful to make plans and policies for the development of the municipality. The study concentrates on overviews of the municipality’s existing condition and cannot include all aspects in-depth; therefore to fulfill the gap of this study; the researcher recommends that research should be done one by one in every sector in detail.